(untitled) (Eduscotech, 2024)
This research aimed to determine whether or not outdoor learning through relay flag game can improve children cooperation play group Wijaya Kusuma, Pilangkenceng district Madiun Regency. Subject in this research were all of the children play group Wijaya Kusuma, Pilangkenceng district Madiun Regency. The number of student who studdied 18 children. There 6 girls and 12 boys. Technigue of collecting data used interview, observation and documentation. Technigue of analysis data that is used in this research was assessment sheet that was observation sheet which useful to record observation directly to the object of research. The results shown the pre cycle learning process, first cycle and second cycle can be concluded that in this research was successful because in the second cycle has exceeded the target score, that was improvement children cooperation through relay flag game with completeness score that reached more that 80 % of children from all of the children play group Wijaya Kusuma, Pilangkenceng district Madiun Regency.